O teletrabalho e as doenças ocupacionais na perspectiva dos direitos fundamentais e do direito à desconexão - Moreira, Maria Gabriela Silva (2022)
The present dissertation aimed to discuss the fundamental right of work, verifying the increase in occupational diseases, work overload, stress and the non-restriction between working time and free time, in addition to analyzing the effectiveness of rights fundamental work, through the use of the right to disconnect. We investigated the historical evolution of telework in Labor Law, which employees reinvented themselves in the face of major technological changes, in this way, it was an analysis from its model made to its modification in Brazilian legislation. Then, it dealt with the act of formalizing the bond between employer and employee, starting with the hiring and the risks involved in the employment relationship, it was treated about the advantages and disadvantages faced in the daily life of teleworkers, the obstacles to health, for the work environment, for private and/or professional life, also, the increase in occupational diseases due to daily isolation, stress, overload, leading to pathologies such as Burnout syndrome, depression, among others. They were discussed about the effectiveness or not of the fundamental rights of the employees, in the context of the principle of equality and the fundamental rights of the worker foreseen in the Constitution of the Federal Republic of 1988. Another point researched and analyzed was the right to disconnect, which is a right of all employees to leave work after a certain workload agreed between employee and employer, being very important for the quality of the worker's physical and psychological life, such as which for the preservation of their social life and their family life. The flexibility of teleworking was embodied in a pandemic context, and, with COVID-19, many workers continued to perform their functions from inside their homes, avoiding the contagion and spread of the pandemic, however, innovative ways and the use of technologies must have the objective of achieving economic growth and realizing the social value of work and human dignity. One of the most important points is valuing human work and enforcing the fundamental rights of employees. For this to happen, companies are an essential part of this process, offering training and qualified professionals in the health area to accompany employees, becoming a prevention, leading to decent and healthy work. It is necessary to prevent and make use of practices that are correct, to extinguish psychosocial risks at work. The right to disconnect for teleworkers means reducing the risk of depression, suicide attempts and suicides, which are quite common pathologies in the workplace, due to non-disconnection and necessary and mandatory rest between one day and another. According to the WHO, depression will be the most disabling illness by the mid-2030s, and nearly 10% of that factor will be because of the work environment. Therefore, the work environment needs to seek to protect the basic rights of employees, for an environment that applies fundamental and labor rights in a healthy and dignified way. The deductive method and the techniques of bibliographic and documentary research were used.